Pseudomonas aeruginosa infection in an intensive care unit - Burjanadze, Irma; Kurtsikashvili, Giorgi; Tsereteli, David; Tsertsvadze, Ekaterina; Kekelidze, Merab; Imnadze, Paata; Besser, John; Rhame, Frank; Toscano, William A; O’Boyle, Carol (International Journal of Infection Control, 2007)
P. aeruginosa is a well-known cause of hospital-acquired pneumonia (HAP) in intensive care units (ICU). We conducted an epidemiologic and molecular investigation of endemic P. aeruginosa infection in an ICU. P. aeruginosa strains isolated from hospitalized patients and environmental samples in the ICU of the National Medical Center (NMC) were collected by the hospital infection laboratory of National Center for Disease Control and Public Health, October 2005 - April 2007. The antimicrobial susceptibility of the isolates in vitro was assessed by an agar disk diffusion method, as recommended by the Clinical and Laboratory Standards Institute. The antimicrobial susceptibility data were analyzed using WHONET software. Isolates resistant to cefepime, imipenem, aztreonam, ciprofloxacin, piperacillin, and gentamicin were defined as multidrug resistant (MDR). P. aeruginosa was isolated 89 specimens obtained from 53 patients with HAP. The incidence rate of MDR P. aeruginosa infection was 15,8/100 patient admissions per year. MDR strains were common, making up 28/89 (31,5%) of all P. aeruginosa isolates in this study. In March - August 2006 there was an outbreak of HAP caused by P. aeruginosa. During the outbreak from 25 patients with HAP have been isolated P. aeruginosa. Using PFGE typing, it was observed that twelve P. aeruginosa had same genetic pattern. Environmental investigations demonstrated the presence of P. aeruginosa in the ventilation equipment. In one case, MDR P. aeruginosa was found in microfilter of AV machine. The most predominant etiologic factor responsible for HAP in ICU of NMC was endemic P. aeruginosa